Searching for the Fusarium spp. which are responsible for trichothecene contamination in oats. Using metataxonomy to compare the distribution of toxigenic species in fields from Spain and the UK - Gil-Serna, Jéssica; Patiño, Belén; Verheecke-Vaessen, Carol; Vázquez, Covadonga; Medina, Angel (MDPI, 2022)
The contamination of oats with Fusarium toxins poses a high risk for food safety. Among them, trichothecenes are the most frequently reported in European oats, especially in northern countries. The environmental conditions related to the climate change scenario might favour a distribution shift in Fusarium species and the presence of these toxins in Southern European countries. In this paper, we present an ambitious work to determine the species responsible for trichothecene contamination in Spanish oats and to compare the results in the United Kingdom (UK) using a metataxonomic approach applied to both oat grains and soil samples collected from both countries. Regarding T-2 and HT-2 toxin producers, F. langsethiae was detected in 38% and 25% of the oat samples from the UK and Spain, respectively, and to the best of our knowledge, this is the first report of the detection of this fungus in oats from Spain. The relevant type B trichothecene producer, F. poae, was the most frequently detected Fusarium species in oats from both origins. Other important trichothecene producers, such as the Fusarium tricinctum species complex or Fusarium cerealis, were also frequently detected in oat fields. Many Fusarium toxins, including T-2 and HT-2 toxins, deoxynivalenol, or nivalenol, were detected in oat samples. The results obtained in this work revealed a clear change in the distribution of trichothecene producers and the necessity to establish the potential of these species to colonize oats and their ability to produce mycotoxins.
Keywords: metataxonomy; Fusarium; trichothecenes; T-2 toxin; HT-2 toxin; deoxynivalenol; soil